2022
DOI: 10.3390/ijerph192114412
|View full text |Cite
|
Sign up to set email alerts
|

Sports and Social Interaction: Sports Experiences and Attitudes of the Urban Running Community

Abstract: Social change and development influence the motivational factors of people’s sports participation, exposing the need for socialization and interaction. The purpose of this study is to investigate the interaction pattern of the urban running community and the behavior pattern of runners with the help of social interaction theory, and to explore the inner connection between their community movement and social interaction. Ten senior members of marathon urban running societies were selected to conduct two rounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Previous research suggested that team sports could promote social network formation and bonding, leading to improved team performance and personal growth. 16,17 The lack of recognition might be due to the misconception that competitive team sports only benefit athletes and not the general student population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggested that team sports could promote social network formation and bonding, leading to improved team performance and personal growth. 16,17 The lack of recognition might be due to the misconception that competitive team sports only benefit athletes and not the general student population.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no research has comprehensively uncovered the impact of social interactions on the performance of sport organisations in this particular and diverse region. Recent findings from more global research suggest that social interaction factors such as self-examination, adaptability to group members, sense of group belonging, and online social interaction networks have a significant impact on influencing the performance of sport organisations (Sauer & Ed, 2017;Yang et al, 2022). This research, with a focus on Ambon City, has a strong urgency to fill the knowledge gap that still exists.…”
Section: Introductionmentioning
confidence: 97%
“…Emotional support from the family generates an important support base for athletes to face the challenges of the sporting context [1]. However, the excessive pressure and demands found in the family environment act as a demotivator to practice sports [2]. Considering this complex duality, this research seeks to understand how the family participates in the players' development process, with a specific focus on a state football league in Brazil.…”
Section: Introductionmentioning
confidence: 99%